Accelerating regional trade integration in Africa through regional value chains: A SADC perspective - Nare, Boitumelo (Graduate School of Business (GSB), 2021)
Regional integration has been a key ambition, vision and standing agenda of the African continent for the past two decades. The recent signing of the Africa Continental Free Trade Agreement (AfCFTA) (signed by 54 of the 55 members of the African Union as of July 2019) brings to the fore the urgent need to accelerate the implementation of what has been thus far an elongated period of planning and discussion. One of the key mandates of the AfCFTA is to ensure acceleration of intra-African trade and boost Africa's trading position in the global market by strengthening Africa's common voice and policy space in global trade negotiations (African Union, 2018). Intra-regional trade can be considered as a quick avenue for the continent and its respective Regional Economic Communities (RECs) such as the Southern African Development Community (SADC), to implement this agenda by leveraging collective resources and opportunities such as increased focus on the establishment of regional value chains (RVCs). Currently, the SADC region has been at the forefront of driving regional trade integration (RTI) in the continent; however, intra-regional trade is still only but a fraction of the RECs total global trade, averaging 5-7% of total trade in 2015-2017. Because of the myriad of challenges in the region – including but not limited to the low rate of RTI, poor infrastructure, poor institutions, unstable political environments, and slow economic growth – RECs, let alone the continent as a whole, cannot take part in and capitalise on the opportunities from complex trade networks through global and regional value chains. Moreover, when African countries do participate in global value chains, they find themselves at the lower end of the value chain where it is harder to reap the benefits due to the unequal distributional effects of such trade activities. This study therefore examined the key factors that drive RTI, and sought to ascertain the relationship between regional value chains and regional trade integration. Lastly, the study aimed to uncover the contribution to economic growth of such trade activities. Thirteen SADC countries are observed over the period 2000-2017 using panel data analysis and various key estimation techniques to ensure robustness of the models used. The study finds that there are definitely key factors that drive regional trade integration in the REC that require increased focus from policy makers and trade activity participants as they have the potential to change the trajectory of the region and the continent's trade landscape. The study also indisputably finds a two-way relationship between RTI and RVCs, suggesting that if key aspects of these activities are addressed, this would lead to a mutual increase in iv these factors as they are highly complementary activities. Lastly, the study confirms the positive impact that RTI and RVCs would have on economic growth attributed to an increase in the level of productive economic trade activity thereby contributing to the gross domestic product (GDP) of countries as individuals and as a collective. The study therefore concludes that there should be more focus from policy makers and all key trade activity stakeholders on driving regional trade integration and participation in regional value chains as the benefits could prove highly rewarding to the SADC RECs and the continent as a whole. Such increased focus will ensure that the region is fully capitalising on the unique strengths of the African continent and driving collective growth and development.